2018
DOI: 10.4314/jae.v22i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of agricultural information sources and adoption of animal and crop technologies among farming households in Imo State, Nigeria

Abstract: The study ascertained effect of utilization of agricultural information sources on adoption of animal and crop technologies among farming households in Imo State, Nigeria. Structured interview schedule was used to collect data from one hundred and fifty respondents using a multi-stage sampling technique. Data were analyzed using both descriptive and inferential statistics: PPMC and t test. Respondent's mean age was 48 years; 99.1% had contact with extension agents; 88.4% had access to between 1 and 5 hectares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Farmers who use market information to make decisions on how to rear pigs tend to have a higher innovative activity, which translates into better competitiveness. This finding is in line with the study by (Uwandu et al, 2018) in which agricultural information utilisation was found to enhance farmer innovativeness in Imo State, Nigeria. Related studies by Adetimehim et al, 2018in Indo State, Nigeria, Acheampong et al, 2017 in Ejisu-Juaben Municipality of Ghana and (Aonngernthayakorn & Pongquan, 2017) in central Thailand confirmed a relationship between access to extension service and utilisation of agricultural information.…”
Section: Discussionsupporting
confidence: 91%
“…Farmers who use market information to make decisions on how to rear pigs tend to have a higher innovative activity, which translates into better competitiveness. This finding is in line with the study by (Uwandu et al, 2018) in which agricultural information utilisation was found to enhance farmer innovativeness in Imo State, Nigeria. Related studies by Adetimehim et al, 2018in Indo State, Nigeria, Acheampong et al, 2017 in Ejisu-Juaben Municipality of Ghana and (Aonngernthayakorn & Pongquan, 2017) in central Thailand confirmed a relationship between access to extension service and utilisation of agricultural information.…”
Section: Discussionsupporting
confidence: 91%
“…Radio has been found to be one broadcast medium identified by almost all experts to be the most appropriate for rural liberation programmes. It cuts across distance as Uwandu, Thomas and Okoro (2018) found that mass media, especially radio play an important role in creating awareness about new agricultural technologies among farming communities across the world and thus has immediate effect. It has been considered the only medium of mass communication the rural population is familiar with (Yahaya, Adamson and Kareem, 2018).…”
mentioning
confidence: 99%
“…Subsequently, all national agricultural intervention programme till date have made use of radio as potent tool of touching base with the targets and beneficiaries of development oriented programme in health, agriculture and environment. Uwandu et al (2018) observes that radio programmes are usually timely and capable of extending messages to target audience irrespective of location thereby bridging gaps that are palpable with difficult terrain, distance, topography, time and socio-political exigencies. The apparent innumerable advantages of radio over other mass media had endeared it to development and social workers, governments and non-government concerns who have continued to exploit such benefits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Information is an indispensable factor in the practice of farming and agricultural information is needed for overall development of agriculture and improvement of living standard of farmers (Uwandu, Thomas & Okoro, 2018). Timely, credible and relevant agricultural information is crucial because it affords farmers opportunity to make and execute wise decisions on their farms which consequently bring about improvement in farm output, yield and income.…”
Section: Introductionmentioning
confidence: 99%